PENGARUH INDEPENDENSI DAN EFEKTIVITAS KOMITE AUDIT TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010 – 2012) - Redhiena Pangestika; Sri Luna Murdianingrum (Program Magister Akuntansi Unsyiah, 2014)
ABSTRACT Financial statement has been the means of communicating financial information to the external parties of the corporation. The financial statement has been expected to be able to provide information for the investors and the creditors for making decisions in relation to the investment of their fund. During the composition of the financial statement, an accrual base has been selected because the base has been more rational and fair in depicting the real company’s financial condition; on the other hand, the use of accrual base might provide more flexibility to the managerial boards in terms of selecting the accounting methods as far as the methods do not go against governing Standards of Financial Accounting. The accounting methods intentionally selected by the managerial boards for certain objectives have been known as earnings management. The behaviors of managerial boards that perform the profit management might be minimized by implementing the corporate governance. The mechanism of corporate governance has been marked by the existence of audit committee.The research was performed in order to find the influence of audit committee independence, audit committee expertise, audit committee meeting frequency and audit committee age toward the profit management. The research was performed in the manufacture companies enlisted in the Indonesian Stock Exchange from 2010 – 2012.The results of the research showed that the audit committee independence, the audit committee expertise and the audit committee meeting frequency had influence toward earnings management; on the contrary, the audit committee age did not have influence toward the earnings management. Keyword : Earnings management, audit committee independence, audit committee expertise, audit committee meeting frequency, audit committee age